Development and validation of a measure of consumer behaviors toward nutritional labeling in restaurants. Issue 5 (20th October 2017) - Kim, Eojina; Ham, Sunny
ABSTRACT: This study identifies multiple steps for the development and validation of a measurement of consumer attitudes and behaviors regarding nutritional information in restaurants. These steps include an extensive literature review, in-depth interviews, experts' reviews, a pilot test, and a customer survey. The final questionnaire that collected data from 617 restaurant customers was verified through statistical analysis of reliability test, construct validity, and confirmatory factor analysis. The measurement offers a method to evaluate customers' use of nutrition information in restaurants and, thus, a tool to prevent obesity for the public.